Images in law - Wagner, Anne (Ashgate, 2006)
Deep structures of empire : notes on imperial machines and bodies -- Intervention and the new imagery of world order -- Key words in Chinese law -- Visual semiotics of court dress in England and Wales : failed or successful vector of professional identity? -- The drama of the courtroom -- Digital visual and multimedia software and the reshaping of legal knowledge -- A Las Menimas for the law -- Legal language in action : raising basic awareness about and understanding of competing legal system in the legal classroom -- Discourses of the ideal and the actual in the courtroom : the conflict for jurors in 'making sense' of general instructions -- Jurors' recorded deliberations : an analysis -- "Let me see your hands" : the grammar of physical control in police directives -- Images of the Irish family : a 'slightly' constitutional arrangement -- Images of racial discrimination France -- Law's trouble with images : fetishism and seduction from Athens and Jerusalem to Madison Avenue